Assessing the health of the nephron in acute kidney injury: biomarkers of kidney function and injury. Issue 6 (November 2019) - Menez, Steven; Parikh, Chirag R.
Abstract : Purpose of review: Serum creatinine and urine output continue to be the mainstays of diagnosis of acute kidney injury, though both of these measures have significant limitations, especially in acutely hospitalized patients. Biomarkers in both blood and urine have been studied extensively in the research setting and are on the verge of clinical practice to improve diagnosis of AKI. Recent findings: Blood and urine biomarkers can be localized to specific areas or functions within the nephron. Biomarkers can help to characterize glomerular or tubular function; glomerular, tubular, or interstitial injury; inflammation; or repair. Further, biomarkers can improve diagnosis of AKI in various clinical settings including acute interstitial nephritis, acute tubular injury, and hepatorenal syndrome, and cardiorenal syndrome. Summary: Biomarkers are becoming more prevalent in both research and getting close to clinical use. Both blood and urine biomarkers can help to localize impairment in nephron health by either location or function within the nephron and among various causes of AKI.